Black power on campus : the University of Illinois, 1965-75 - Williamson-Lott, Joy Ann, 1971- (University of Illinois Press, 2003)
"Joy Williamson charts the evolution of Black consciousness on predominately white American campuses during the critical period between the mid-sixties and mid-seventies, with the Black student movement at the University of Illinois at Urbana-Champaign (UIUC) serving as an illuminating microcosm of similar movements across the country." "As Williamson shows, increased university admission rates in the late 1960s did not lead to increased acceptance for Black students. In response to institutional apathy, or even hostility, Black students advocated Black unity, celebrated Black culture, and employed aggressive tactics to initiate a period of institutional reform during one of American higher education's most tempestuous eras. Williamson examines the creation of such groups as the Black Students Association at UIUC and looks at the effect the activities of such groups had on the wider student body, on academic administrators, and on university policies. Drawing on student publications of the late 1960s and early 1970s, as well as interviews with former administrators, faculty, and student activists, Williamson discusses the emergence of Black Power ideology, what constitutes "Blackness," and notions of self-advancement versus racial solidarity. Promoting an organic understanding of social protest and assessing the impact of Black student activism on an American campus, Black Power on Campus is an important contribution to the broader literature on African American liberation movements, the role of Black youth in protest movements, and the reform of American higher education."--Jacket